S91 Probing ventilation/perfusion properties with dynamic susceptibility contrast 19F-MRI of inhaled perfluoropropane. (December 2018) - Pippard, B; Neal, M; Simpson, AJ; Thelwall, P
Abstract : Introduction: 19 F-MRI of inhaled perfluoropropane (PFP) is an emerging approach to ventilation imaging in humans, enabling assessment of regional gas distribution without the need for hyperpolarization. PFP signal intensity is strongly influenced by magnetic susceptibility differences at gas-tissue interfaces, resulting in rapid signal decay (short T2 * ) during 19 F-MR image acquisition. Previous pre-clinical studies have reported the ability to reduce susceptibility differences in the lung using intravenous paramagnetic contrast agents. 1 2 We hypothesized that administration of a widely-used MR contrast agent (Gadobutrol) could raise the T2 * and signal intensity of inhaled PFP gas, owing to magnetic susceptibility matching in well perfused and well ventilated regions of the lung. Methods: 6 healthy volunteers (5 M, 1F; aged 26–34) provided written informed consent and were screened for study eligibility. Participants underwent a single MRI scan session, involving periodic inhalation of a 79% PFP/21% oxygen gas mixture. Inhalations comprised three deep breaths of gas followed by a breath-hold. During one inhalation, participants were administered an intravenous dose of Gadobutrol (0.2 mmol/kg), concurrent with the start of breath-hold. Heart rate and oxygen saturations were monitored throughout. MRI scans were acquired using a 3T scanner and 19 F surface coil. Results: Dynamic unlocalised spectroscopy was performed in two participants, demonstrating a transient rise in PFP T2 * following Gadobutrol administration (figure 1a). Dynamic 2D image acquisitions were performed in the remaining participants, showing a corresponding increase in PFP signal intensity shortly after contrast administration (figure 1b). All scans were well tolerated, with no adverse events. Conclusions: We have demonstrated that the T2 * of inhaled PFP increases following administration of an intravenous paramagnetic contrast agent, reflecting transient magnetic susceptibility-matching at the gas-tissue interface. To our knowledge, this is the first in man demonstration of this concept. Our findings offer potential to assess lung microvascular perfusion properties through observed changes in PFP signal intensity, presenting a novel, radiation-free approach to combined ventilation/perfusion assessment at the alveolar level. Future studies will compare the utility of this technique with more established clinical ventilation/perfusion measurements. References: Vignaud A, et al. Magn Reson Med2005;54:28–33. Dimitrov IE, et al. J Magn Reson Imaging2005;21:149–155.